Ab initio study of topological surface states of strained HgTe - Wu, Shu-Chun; Yan, Binghai; Felser, Claudia (EPL - Europhysics Letters, 2014)
The topological surface states of mercury telluride (HgTe) are studied by ab initio calculations assuming different strains and surface terminations. For the Te-terminated surface, a single Dirac cone exists at the Γ-point. The Dirac point shifts up from the bulk valence bands into the energy gap when the substrate-induced strain increases. At the experimental strain value (0.3%), the Dirac point lies slightly below the bulk valence band maximum. A left-handed spin texture was observed in the upper Dirac cone, similar to that of the Bi2Se3-type topological insulator. For the Hg-terminated surface, three Dirac cones appear at three time-reversal-invariant momenta, excluding the Γ-point, with non-trivial spin textures.
CRIS-Team Scopus Importer:2023-03-20